Olefin metathesis in nano-sized systems - Astruc, Didier; Diallo, Abdou K.; Gatard, Sylvain; Liang, Liyuan; Ornelas, Cátia; Martinez, Victor; Méry, Denise; Ruiz, Jaime (Beilstein Journal of Organic Chemistry, 2011)
The interplay between olefin metathesis and dendrimers and other nano systems is addressed in this mini review mostly based on the authors’ own contributions over the last decade. Two subjects are presented and discussed: (i) The catalysis of olefin metathesis by dendritic nano-catalysts via either covalent attachment (ROMP) or, more usefully, dendrimer encapsulation – ring closing metathesis (RCM), cross metathesis (CM), enyne metathesis reactions (EYM) – for reactions in water without a co-solvent and (ii) construction and functionalization of dendrimers by CM reactions.
Keywords: dendrimer; green chemistry; metathesis; nano-system; water

Handbook of Metathesis - Grubbs, R. H. (Wiley-VCH, 2002)

(untitled) - Chauvin, Y. (Angew. Chem., Int. Ed., 2006)

(untitled) - Schrock, R. R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Grubbs, R. H. (Angew. Chem., Int. Ed., 2006)

(untitled) - Fürstner, A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2000)

(untitled) - Astruc, D. (New J. Chem., 2005)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

Organometallic Chemistry and Catalysis - Astruc, D. (Springer, 2007)

(untitled) - Wijkens, P.; Jastrzebski, J. T. B. H.; van der Schaaf, P. A.; Kolly, R.; Hafner, A.; van Koten, G. (Org. Lett., 2000)

(untitled) - Garber, S. B.; Kingsbury, J. S.; Gray, B. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Beerens, H.; Verpoort, F.; Verdonck, L. (J. Mol. Catal. A: Chem., 2000)

(untitled) - Beerens, H.; Verpoort, F.; Verdonck, L. (J. Mol. Catal. A: Chem., 2000)

(untitled) - Sanford, M. S.; Ulman, M.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Hansen, S. M.; Volland, M. A. O.; Rominger, F.; Eisenträger, F.; Hofmann, P. (Angew. Chem., Int. Ed., 1999)

(untitled) - Hansen, S.; Rominger, F.; Metz, M.; Hofmann, P. (Chem.–Eur. J., 1999)

(untitled) - Adlhart, C.; Volland, M. A. O.; Hofmann, P.; Chen, P. (Helv. Chim. Acta, 2000)

(untitled) - Amoroso, D.; Fogg, D. E. (Macromolecules, 2000)

(untitled) - Six, C.; Beck, K.; Wegner, A.; Leitner, W. (Organometallics, 2000)

(untitled) - Reetz, M. T.; Lohmer, G.; Schwickardi, R. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Alonso, E.; Astruc, D. (J. Am. Chem. Soc., 2000)

(untitled) - Kingsbury, J.; Harrity, J. P. A.; Bonitatebus, P. J.; Hoveyda, A. H. (J. Am. Chem. Soc., 1999)

(untitled) - Gatard, S.; Nlate, S.; Cloutet, E.; Bravic, G.; Blais, J.-C.; Astruc, D. (Angew. Chem., Int. Ed., 2003)

(untitled) - Gatard, S.; Kahlal, S.; Méry, D.; Nlate, S.; Cloutet, E.; Saillard, J.-Y.; Astruc, D. (Organometallics, 2004)

(untitled) - Méry, D.; Astruc, D. (J. Mol. Catal. A: Chem., 2005)

(untitled) - Lemo, J.; Heuzé, K.; Astruc, D. (Org. Lett., 2005)

(untitled) - Astruc, D.; Heuzé, K.; Gatard, S.; Méry, D.; Nlate, S.; Plault, L. (Adv. Synth. Catal., 2005)

(untitled) - Heuze, K.; Méry, D.; Gauss, D.; Astruc, D. (Chem. Commun., 2003)

(untitled) - Heuzé, K.; Méry, D.; Gauss, D.; Blais, J.-C.; Astruc, D. (Chem.–Eur. J., 2004)

(untitled) - Lemo, J.; Heuzé, K.; Astruc, D. (Chem. Commun., 2007)

(untitled) - Trujillo, H. A.; Casado, C. M.; Astruc, D. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Trujillo, H. A.; Casado, C. M.; Ruiz, J.; Astruc, D. (J. Am. Chem. Soc., 1999)

(untitled) - Moulines, F.; Astruc, D. (Angew. Chem., Int. Ed. Engl., 1988)

(untitled) - Moulines, F.; Djakovitch, L.; Boese, R.; Gloaguen, B.; Thiel, W.; Fillaut, J.-L.; Delville, M.-H.; Astruc, D. (Angew. Chem., Int. Ed. Engl., 1993)

(untitled) - Catheline, D.; Astruc, D. (J. Organomet. Chem., 1983)

(untitled) - Catheline, D.; Astruc, D. (J. Organomet. Chem., 1984)

(untitled) - Lacoste, M.; Rabaa, H.; Astruc, D.; Le Beuze, A.; Saillard, J.-Y.; Précigoux, G.; Courseille, C.; Ardoin, N.; Bowyer, W. (Organometallics, 1989)

(untitled) - Martinez, V.; Blais, J.-C.; Astruc, D. (Org. Lett., 2002)

(untitled) - Martinez, V.; Blais, J.-C. (Angew. Chem., Int. Ed., 2003)

(untitled) - Martinez, V.; Blais, J.-C.; Bravic, G.; Astruc, D. (Organometallics, 2004)

(untitled) - Astruc, D.; Ruiz, J. (Tetrahedron, 2010)

(untitled) - Ornelas, C.; Méry, D.; Ruiz Aranzaes, J.; Blais, J.-C.; Cloutet, E.; Astruc, D. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ornelas, C.; Méry, D.; Cloutet, E.; Ruiz Aranzaes, J.; Astruc, D. (J. Am. Chem. Soc., 2008)

(untitled) - Beil, J. B.; Lemcoff, N. G.; Zimmerman, S. C. (J. Am. Chem. Soc., 2004)

(untitled) - Lemcoff, N. G.; Spurlin, T. A.; Gewirth, A. A.; Zimmerman, S. C.; Beil, J. B.; Elmer, S. L.; Vandeveer, H. G. (J. Am. Chem. Soc., 2004)

(untitled) - Wendland, M. S.; Zimmerman, S. C. (J. Am. Chem. Soc., 1999)

(untitled) - Aldama, J.; Wang, Y.; Peng, X. (J. Am. Chem. Soc., 2001)

(untitled) - Wang, Y. A.; Li, J. J.; Chen, H.; Peng, X. (J. Am. Chem. Soc., 2002)

(untitled) - Guo, W.; Li, J. J.; Wang, Y. A.; Peng, X. (J. Am. Chem. Soc., 2003)

Dendrimers and Nanosciences, C. R. Chimie - Guo, W.; Peng, X. (Elsevier, 2003)

(untitled) - Sartor, V.; Djakovitch, L.; Fillaut, J.-L.; Moulines, F.; Neveu, F.; Marvaud, V.; Guittard, J.; Blais, J.-C.; Astruc, D. (J. Am. Chem. Soc., 1999)

(untitled) - Ruiz, J.; Lafuente, G.; Marcen, S.; Ornelas, C.; Lazare, S.; Blais, J.-C.; Cloutet, E.; Astruc, D. (J. Am. Chem. Soc., 2003)

(untitled) - Burtscher, D.; Grela, K. (Angew. Chem., Int. Ed., 2009)
Review on olefin metathesis in water and aqueous solvents.

(untitled) - Connon, S. J.; Rivard, M.; Zaja, M.; Blechert, S. (Adv. Synth. Catal., 2003)

(untitled) - Michrowska, A.; Gulajski, L.; Kaczmarska, Z.; Mennecke, K.; Kirschning, A.; Grela, K. (Green Chem., 2006)

(untitled) - Binder, J. B.; Blank, J. J.; Raines, R. T. (Org. Lett., 2007)

(untitled) - Gulajski, L.; Sledz, P.; Grela, K. (Green Chem., 2008)
For utrasonification-facilitated metathesis in water.

(untitled) - Mingotaud, A. F.; Krämer, M.; Mingotaud, C. (J. Mol. Cat. A: Chem., 2007)
For Surfactant-facilitated metathesis in water (see also [60-62]).

(untitled) - Lipschulz, B. H.; Aguinaldo, G. T.; Ghorai, S.; Voigtritter, K. (Org. Lett., 2008)

(untitled) - Lipschutz, B. H.; Ghorai, S.; Aguinaldo, G. T. (Adv. Synth. Catal., 2008)

(untitled) - Brendgen, T.; Fahlbusch, T.; Frank, M.; Schühle, D. T.; Sessler, M.; Schatz, J. (Adv. Synth. Catal., 2009)

(untitled) - Diallo, A. K.; Boisselier, E.; Liang, L.; Ruiz, J.; Astruc, D. (Chem.–Eur. J., 2010)

(untitled) - Newkome, G. R.; Yao, Z.; Baker, G. R.; Gupta, V. K. (J. Org. Chem., 1985)

(untitled) - Newkome, G. R.; Moorefield, C. N.; Baker, G. R.; Johnson, A. L.; Behera, R. K. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Davis, K. J.; Sinou, D. (J. Mol. Catal. A: Chem., 2002)

(untitled) - Polshettiwar, V.; Varma, R. S. (J. Org. Chem., 2008)